2012
DOI: 10.4191/kcers.2012.49.1.066
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study on Colorative Mechanism of Ancient Goryeo Celadon Glaze by Mossbauer Spectroscopy and Chromaticity Analysis

Abstract: In ancient Goryeo celadon, the effect of the chemical composition and ionic state of Fe on the color was evaluated by Mössbauer spectroscopy and Design of Experiment (DOE) analysis. The ancient celadon pieces excavated from the kiln sites in GangJin and Buan areas were analyzed by Mssbauer spectroscopy, chromaticity, and DOE analysis. The color of celadon was found to be mainly determined by that of glaze since variations of L*, a*, and b* values for the body were much smaller than those for the glaze. As Fe 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Pink lines refer to ferrihydrite ◂ intense the reduction atmosphere is likley to be established. Accordingly, The analyzed potteries in this study showed the Fe(II)/Fe(II) values between 0.06 and 0.11, which is significantly lower than those of celadon glaze (2.5 -7) fired at a reducing atmosphere [17]. Although the area ratio of Fe(II)/Fe(III) and chromaticity did not show any distinct relationship between the two, it might have been affected by the texture of the surfaces or particle sizes.…”
Section: Phase Of Fe Ionmentioning
confidence: 51%
“…Pink lines refer to ferrihydrite ◂ intense the reduction atmosphere is likley to be established. Accordingly, The analyzed potteries in this study showed the Fe(II)/Fe(II) values between 0.06 and 0.11, which is significantly lower than those of celadon glaze (2.5 -7) fired at a reducing atmosphere [17]. Although the area ratio of Fe(II)/Fe(III) and chromaticity did not show any distinct relationship between the two, it might have been affected by the texture of the surfaces or particle sizes.…”
Section: Phase Of Fe Ionmentioning
confidence: 51%
“…Glaze Colorations can be classified into three types using the Fe form (Hwang, 2008), i.e., ionic colorations (as in the celadon glaze), colloid colorations (as in the tenmoku glaze), and crystal colorations (as in the iron crystal glaze). Scientific analysis of the iron oxide phases during the coloring of a celadon glaze and iron glaze has been conducted using a Mössbauer spectrometer (Hwang, 2008;Jeon et al, 2011;Kim et al, 2010;Pyon, 2005). Raman spectroscopy analysis has also been carried out on Cheolwha Buncheong ware and blackware (Lim, 2013;Park, 2018).…”
Section: Introductionmentioning
confidence: 99%